Platelet Adhesiveness and Euglobulin Lysis Time in Dogs Given Repeated Infusion of Sodium Palmitate - Cucuianu, M; Papilian, V. V; Bareliuc, N; Crisnic, I (Thrombosis and Haemostasis, 1969)
The effect of infusions with sodium palmitate 3.5 m Mol/1 on platelet adhesiveness and euglobulin lysis time was studied in 16 dogs. A decrease of platelet adhesiveness was noted 15 min after infusion. Decreased platelet adhesiveness persisted 3 and 24 hrs later, although platelet counts that were diminished 15 min after the infusion, returned to the initial level. Fibrinogen levels were not found to decrease during infusions of fatty acids. A progressive increase of plasma fibrinogen was even noted in animals that survived more than 7 days after the first infusion. Following a transient acceleration of euglobulin lysis time, a delayed fibrinolysis was noted, probably as a result of the exhaustion of blood activator.Fibrin depositions were emphasized in histological sections. In some animals aspects of obliterative thromboangiitis were noted. However bilateral cortical necrosis was found in only 1 dog.It seems that correlations between increased lipid mobilization and changes of coagulability and fibrinolysis in atherosclerosis are much more complex.